Efecto de cuatro niveles de Fertilización Nitrogenada en el rendimiento de salvia hispanica l. en Virú, La Libertad - Rojas Sánchez, Deysi Elizabeth (2017)
The cultivation of chia (Salvia hispanica) has been considered as one of the crops with greatest potential of expansion recently, due to features such as nutritional quality and agronomic advantages. Since it is a rediscovery crop, the information on agronomic management is not yet very well defined, mainly related to nitrogen fertilization in which could result in a substantial increase in production. Therefore, the goal with this work was to evaluate the effect of four levels of nitrogen on the yield of Salvia hispanica L. in Virú, La Libertad. The experiment was carried out on the demonstration plot of the Chavimochic - Virú Special Project, in the randomized block experimental design with 4 treatments (0, 60, 90 and 120 kg.ha-1 of nitrogen) and four repetitions, evaluating morphological and yield traits. The results showed that all traits evaluated had a significant difference between the nitrogen doses at 5% of probability. The grain yield in treatments with 90 and 120 kg.ha-1 of N (T2 and T3) were those that reached the highest average, with 1009.17 and 1012.17 kg.ha-1 respectively, and there was no significant difference between them. As expected, the lower yield was the T0 with 0 kg.ha-1 of N in which the grain yield was of 288.1 kg.ha-1. We conclude that there is a significant difference among treatments in response to the application of different levels of nitrogen in all traits evaluated and there is a tendency that with the increase of the nitrogen dose the yield also increases until reaching a limit in which larger doses have no significant effect. The information generated by this work could help as a basis for the nitrogen fertilization use in Chia, seeking the increase of production of this crop.